Analysis of the Impact of the Reforms Implemented by the International Monetary Fund - Mario Cuvi Santacruz; Angie Sánchez Erazo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The International Monetary Fund watches over the international monetary system and analyzes issues that could incite instability. It does this through a system called surveillance, by which it monitors, studies, integrates and evaluates data and provides advice on economic policies to its members. This paper explains what surveillance is, its function, importance, and legal regime, it analyzes recent reforms to the system and proposes recommendations on how The Fund should take advantage of these reforms to better influence countries’ decisions and therefore positively affect members´ engagement with Surveillance